Perception of organizational justice regarding the asymmetrical remuneration of employees of an organization in the electrical energy sector - Fabiana Zeferina da Silveira; Alcindo Cipriano Argolo Mendes; Rogério João Lunkes; Edicreia Andrade dos Santos (Revista Ambiente Contábil, 2025)
Purpose: This study sought to verify the perception of employees of an organization in the electric power sector regarding organizational justice regarding remuneration asymmetry. Three dimensions of organizational justice were considered for analysis purposes: distributive, procedural and interactional justice.